Acute confusion in pregnancy - Amanda Hill; Francesca Neuberger (Clinical Medicine)
If a woman is acutely confused in pregnancy, she will most likely present to an unscheduled care setting outside of maternity services. It is therefore essential that all clinicians working within general medicine are comfortable assessing pregnant women in this context. Useful resources are available to support assessing pregnant women who present acutely; however, confusion is beyond their scope. This article discusses important aspects to consider when assessing pregnant women and places emphasis on a systematic approach to ensure that obstetric and non-obstetric causes of confusion have been considered. Certain life-threatening diagnoses have been further discussed in more detail (Wernicke’s encephalopathy, hyponatraemia, hypercalcaemia, acute fatty liver of pregnancy and thrombotic thrombocytopenia purpura). These conditions have been chosen as there is a significant risk of maternal mortality and morbidity as well as poor fetal outcomes if not recognised and treated early.